Recovery of mouse growth hormone from E. coli inclusion bodies using a mild solubilisation and repeated freeze–thaw approach - Minah Kim; Ries J. Langley; Jo K. Perry; Yue Wang (Molecular Biology Reports, 2025)
Background Recombinant mouse GH (mGH) is a critical tool for investigating GH-GH receptor (GHR) interactions in rodent models. However, while numerous methods exist for producing human GH, detailed protocols for the expression and purification of recombinant mGH remain scarce in the literature. Methods We developed a method for refolding mGH from inclusion bodies produced in Escherichia coli ( E. coli ). Recombinant mGH was fused with a N-terminal thioredoxin (Trx) tag and was expressed as inclusion body proteins in E. coli when induced at 30 °C. Inclusion bodies were isolated and solubilised under mild conditions (50 mM Tris–HCl, 2 M urea, pH 10.5) and freeze-thawed. Results Three rounds of freeze-thawing improved solubilisation when compared to a single round. Subsequently, recombinant mGH underwent Trx-tag removal and was purified using anion exchange chromatography to achieve a purity of 98%. Purified mGH displayed circular dichroism spectral profiles comparable to that of commercially sourced mGH, confirming the preservation of the secondary structure in refolded mGH. Bioactivity was confirmed using a Ba/F3-mGhr cell viability assay and showed that refolded mGH had comparable bioactivity to commercially sourced mGH. Bioactivity was also assessed by measuring activation of mGH receptor signal transduction in B16-F10 mouse melanoma cells by phosphorylated STAT5 western blot analysis. Conclusions We present an efficient and cost-effective protocol for mGH production. This repeated freeze–thaw approach may have broad application for other proteins expressed in the form of inclusion bodies for which low yields are observed following a single round of freeze–thaw.